Enantioselective C–H Arylation and Vinylation of Cyclobutyl Carboxylic Amides - Wu, Qing-Feng (ACS Catal, 2018)
Chiral mono-N-protected aminomethyl oxazoline (MPAO) ligands are found to promote enantioselective C–H arylation and vinylation of the cyclobutyl carboxylic acid derivatives via Pd(II)/Pd(IV) redox catalysis. This ligand scaffold overcame two important limitations of the previous MPAHA (mono-N-protected α-amino-O-methylhydroxamic acid) ligands-enabled asymmetric C–H activation/C–C coupling reactions of cyclic carboxylic amides through Pd(II)/Pd(0) catalysis: substrates containing α-hydrogen atoms are not compatible; vinylation has not been developed. Sequential C–H arylation and vinylation of cyclobutanes are also accomplished to construct three consecutive chiral centers on the crowded cyclobutane rings, rendering this reaction highly versatile for the preparation of chiral cyclobutanes.